HACCP - Mortimore, Sara; Wallace, Carol A. [ (Carol Anne)] (Food industry briefing series, 2001)
The Hazard Analysis and Critical Control Point (HACCP) system is a preventative food safety management system, that can be applied throughout the food supply chain from primary production to the consumer. HACCP is internationally recognised as the most effective way to produce safe food, providing a structure for objective assessment of what can go wrong and requiring controls to be put in place to prevent problems. As part of the Blackwell Food Industry Briefing Series, this important book provides a concise, easy-to-use, quick reference aimed at busy food-industry professionals, students or